Gaucher disease: masquerading as chronic malaria - Rai, Seema; Sethi, Gurmeet Kaur; Kumari, Rama; Kaul, Varun (International Journal of Contemporary Pediatrics, 2018)
Gaucher disorder s rare lysosomal disorder characterized by glycolipid laden lysosomes leading to hepatosplenomegaly, bone marrow involvement. Three types of Gaucher disease have been described based on the clinical features, ethnicity and the natural history of the disease. Gaucher disease Type 1 (GD1) occurs mainly in infancy to adulthood and is the commonest lysosomal storage disorder. Gaucher Disease Type II (GD2) and Gaucher disease type III (GD3) patients have onset at less than 1 year, and 2-20 years, respectively.1 GD1 patients do not have neurological involvement. GD2 is the acute neuronopathic and GD3 is the chronic neuronopathic type.